If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(h-3)=2(h+3)
We move all terms to the left:
5(h-3)-(2(h+3))=0
We multiply parentheses
5h-(2(h+3))-15=0
We calculate terms in parentheses: -(2(h+3)), so:We get rid of parentheses
2(h+3)
We multiply parentheses
2h+6
Back to the equation:
-(2h+6)
5h-2h-6-15=0
We add all the numbers together, and all the variables
3h-21=0
We move all terms containing h to the left, all other terms to the right
3h=21
h=21/3
h=7
| 1/x+2/3x=5 | | 4x2+3x-8=0. | | (Q-4)x5=30 | | -113(b+5)=7 | | 7x/(5x+8)=7/9 | | p+8=14.1p | | –2(u–7)=18 | | -6.3n=-25.2n | | –5(z–4)=35 | | 61=5s+11 | | 2/3y+11=-1/3y+8 | | y=1.05^20 | | -8+3x=-16+-13x | | 2x+2x+1x+1x+1x=40 | | 5–(x-2)=4x+17 | | 3m+7-2=8 | | 5-2x=3+x-43x | | 10w=4w+18 | | 10w=(4w+18)/4w | | x=0.25x(-4)x(-1) | | 3(x+3)=6x+1-3x | | 4x^{2}+20x+25=04x2+20x+25=0 | | -13=k2 | | 5x–4=–8x+11 | | x+13=6(x=7) | | `2^(2x+1)-33*2^(x-1)+4=0` | | 8,2-3x=11,7+2x | | 8÷c-8=6 | | c-8÷8=6 | | 10+22,7x=4,7x+28 | | 2x+10=x+28 | | 2x+10=x+284 |